Digital Innovations, Business and Society in Africa New Frontiers and a Shared Strategic Vision - Boateng, Richard; Boateng, Sheena Lovia; Anning-Dorson, Thomas; Olumide Babatope, Longe (Cham : Springer International Publishing : Imprint: Springer, 2022)
For African enterprises, entrepreneurs and governments to take full advantage of new digital opportunities, they need a shared strategic understanding of where they are, what they have, and what they may need to have for the future. This book presents this shared strategic vision to guide future coordinated actions of African enterprises, entrepreneurs, consumers/citizens and governments in using new and emerging digital technologies. It showcases how consumers/citizens, entrepreneurs, organisations, institutions and governments are leveraging new and emerging digital innovations to disrupt and transform value creation and service delivery in Africa.
Part 1. DIGITAL INNOVATION AND VALUE CREATION -- Chapter 1. E-commerce and Globalization: A Bibliometric Review of 24 Years of Research -- Chapter 2. Drones in the Digital Transformation of Healthcare Delivery in Africa -- Chapter 3. Validating Digital Value from Digital Technology Adoption for Entrepreneurial Behaviour in Africa -- Chapter 4. Impact of Mobile Payments on Micro Business Activities: A Developing Country Experience -- Chapter 5. Creating Value in Organizational Communication: Analyzing Twitter Messages for Effective Message Characteristics -- Chapter 6. Dealing with the Unexpected: Exploring the Unintended Negative Consequences of Digitalisation in Africa's Healthcare Industry -- Part 2. DIGITAL DISRUPTION AND TRANSFORMATION -- Chapter 7. Influencer Marketing: A Bibliometric Analysis of 10 Years of Scopus-indexed Research -- Chapter 8. 34 Years of Online Pharmaceutical Marketing Research: A Bibliometric Analysis -- Chapter 9. Platform Business Models: E-logistics Platforms in Sub-Saharan Africa -- Chapter 10. COVID-19 Pandemic and the Small and Medium-sized Enterprise: Digital Strategies for Surviving in a Developing Economy -- Chapter 11. Exploring the Problematic Consumption of Digital Platforms During COVID-19 Pandemic Among University Students in Africa -- Part 3. DIGITAL INNOVATION AND DEVELOPMENT -- Chapter 12. Fairness in the Platform Economy: A Bibliometric Analysis of Journal Research Articles -- Chapter 13. A Review of Dominant Issues, Multi-dimensions, and Future Research Directions for Smart Cities -- Chapter 14. Forecasting Internally Displaced People's Movements with Artificial Intelligence -- Chapter 15. COVID-19: Extracting the Pattern of Morbidity and Mortality Among Countries in the African Region -- Chapter 16. Assessing the Impact of Information and Communication Technologies on Human Development: A Regional Analysis for Africa -- Chapter 17. Hitting the Moving Target: What Information Systems Competencies are Required from Mid-Level Information Systems Managers by Organizations in Sub-Saharan Africa?
Keywords: International business enterprises; New business enterprises; Venture capital; Africa-Economic conditions; International Business; Start-Ups and Venture Capital; African Economics